Penerapan Metode Diskusi Kelompok pada Pelajaran Agama Katolik Materi Peran Sekolah bagi Perkembanganku untuk Meningkatkan Hasil Belajar Siswa Kelas VII SMP Negeri 3 Arso - Bernadeta Marieta (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study was to improve the learning outcomes of seventh grade students of SMP Negeri 3 Arso through the application of the group discussion method in Catholic religion lessons on the role of school material for my development. The type of research to be carried out is Classroom Action Research, this research was conducted at SMP Negeri 3 Arso, Keerom Regency, Papua Province. The research subjects were class VII students totalling 21 people. This research was conducted in the odd semester of the 2024/2025 school year, namely in August 2024. The increase in the average score in Catholic religion subjects, the material on the role of school for my development from cycle 1 to cycle 2 has increased, this shows that the group discussion method can improve the learning outcomes of seventh grade students of SMP Negeri 3 Arso. Based on the results of observations in classroom action research obtained that during the implementation of cycle 1 and continued cycle 2 changes occurred, namely that the average score of students increased from 69.23 in cycle 1 increased to 72.71 in cycle 2, the results of student scores reached the KKM which is 70, so that the group discussion learning model can improve the learning outcomes of students in grade VII SMP Negeri 3 Arso.